(untitled) - Da Prato, Giuseppe (Cambridge, UK, 2002)
Second order linear parabolic and elliptic equations arise frequently in mathematical physics, biology and finance. Here the authors present a state of the art treatment of the subject from a new perspective. They then go on to discuss how the results in the book can be applied to control theory. This area is developing rapidly and there are numerous notes and references that point the reader to more specialized results not covered in the book. Coverage of some essential background material helps to make the book self contained.
Keywords: Differential equations, Partial,Hilbert space,Phương trình vi phân, Phần riêng,Không gian Hilbert